The Influence of Parkinson’s Disease Motor Symptom Asymmetry on Hand Performance: An Examination of the Grooved Pegboard Task - Sara M. Scharoun; Pamela J. Bryden; Michael D. Sage; Quincy J. Almeida; Eric A. Roy (Parkinson's Disease)
This study examined the influence of motor symptom asymmetry in Parkinson’s disease (PD) on Grooved Pegboard (GP) performance in right-handed participants. The Unified Parkinson’s Disease Rating Scale was used to assess motor symptoms and separate participants with PD into two groups (right-arm affected, left-arm affected) for comparison with a group of healthy older adults. Participants completed the place and replace GP tasks two times with both hands. Laterality quotients were computed to quantify performance differences between the two hands. Comparisons among the three groups indicated that when the nonpreferred hand is affected by PD motor symptoms, superior preferred hand performance (as seen in healthy older adults) is further exaggerated in tasks that require precision (i.e., place task). Regardless of the task, when the preferred hand is affected, there is an evident shift to superior left-hand performance, which may inevitably manifest as a switch in hand preference. Results add to the discussion of the relationship between handedness and motor symptom asymmetry in PD.